PHYSIOTHERAPISTS ATTIRE: DOES IT AFFECT PATIENTS COMFORT, CONFIDENCE AND OVERALL PATIENT-THERAPIST RELATIONSHIP (International Journal of Physiotherapy, 2015)
Background: Attire is one of the major determinants of appearance and a key element of non-verbal communication that plays a critical role in the establishment and sustainability of therapeutic relationships. This study aimed to determine the patients’ preferred physiotherapists’ attire and the effect of physiotherapists’ attire on patients’ confidence, comfort and patient-therapists relationship.Methods: A questionnaire was used to collect data in this cross sectional study design. Patients (N=281) attending outpatients physiotherapy clinics in six selected tertiary health institutions in North-eastern Nigeria completed a questionnaire consisting of two sections. Section one solicited sociodemographic information while in section two patients rated their level of confidence and comfort with physiotherapists based on a photo pictures of a male and a female physiotherapists models in four different attires. Descriptive statistics were performed to characterize participants and the differences in patients’ confidence and comfort level by different types of attire were assessed using chi-square. The correlation between physiotherapists’ attire and patient-physiotherapist relationship was determined using spearman rank correlation.Results: Overwhelming majority of the participants were more comfortable (91.1%) and more confident (89.0%) with the physiotherapists dressed in white coat, while they were less comfortable and less confident when their therapists are dressed in suit, native or casual wear. Positive patient-therapist relationship was observed with white coat dressed physiotherapists; while the relationship with business, native and casual wears were inverse.Conclusion: The study supports for continuing recommendation of lab coat as a professional dressing for physiotherapists in Nigeria and affirms the importance of professional dressing in patient-therapists relationship.